Mineral insulated cables and their terminations with a rated voltage not exceeding 750 V - Part 2 Terminations
Specifies requirements for terminations for use with mineral insulated cables complying with the requirements of IEC 60702-1. This consolidated version consists of the second edition (2002) and its amendment 1 (2015). Therefore, no need to order amendment in addition to this publication.